Subglottic stenosis in paediatric patients - Swain, Santosh Kumar; Sahu, Mahesh Chandra; Choudhury, Jasashree (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Subglottic stenosis (SGS) is a complex and challenging clinical entity for paediatric otolaryngologists. Subglottic stenosis is a congenital or acquired lesion characterised by narrowing of the airway extending from the lower free border of the vocal folds to the lower border of the cricoid cartilage. The most common cause of SGS is prolonged endotracheal intubation. The treatment option for SGS is often surgery, which may be endoscopic or open. Nowadays, the endoscopic approach is reaching its limit, and open surgery is advised only in failed cases of endoscopic approach. In this review article, we discuss the current concept and recent advances in the diagnosis and treatment of SGS.